Commercial cosmopolitanism? : cross-cultural objects, spaces, and institutions in the early modern world - Gottmann, Felicia, 1982- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book showcases the wide variety of commercial cosmopolitan practices that arose from the global economic entanglements of the early modern period. In so doing, it demonstrates robust alternatives to the universalising western imperial model of the later period. Deploying a number of interdisciplinary methodologies, chapters provide agency-centred evaluations of the risks and opportunities inherent in the ambiguous role of the cosmopolitan, who operated in between and outside established legal, social, and cultural systems. The book will be important reading for students and scholars working at the intersection of economic, global, and cultural history during this period"--
OCLC-licensed vendor bibliographic record.
Keywords: Economic history -- 1600-1750.; Economic history -- 1750-1918.; Cosmopolitanism -- History; HISTORY / World; BUSINESS & ECONOMICS / Economic History; HISTORY / General